Development of Interactive E-Modules Based on Google Sites to Improve Critical Thinking Skills and Agility at SMKN 2 Jember - Fierman Pradityo Utama Putra; Eges Triwahyuni; Hariyanto (Postgraduate, University of Mataram, 2025)
The purpose of the research is to develop interactive e-modules, product feasibility, and the effectiveness of using Interactive E-modules in class X TAB at SMKN 2 Jember. This research is a Research and Development (R&D), using the ADDIE model approach, which consists of five levels, namely analysis, design, development, implementation, and evaluation. The results of the study indicate that the Interactive E-module media is feasible to use at SMKN 2 Jember. The results of the validation assessment showed a percentage of media component feasibility of 94.67% and material component validation of 95.56%, so it can be categorized as